Optimization of Fermentation and Transcriptomic Analysis: The Impact of Aspartic Acid on the Antioxidant Activity of Termitomyces - Jingfei Zhou; Wenhui Yi; Yunfan Yang; Jiahui Peng; Wujie Zhong; Xuefeng Xu (Fermentation)
Termitomyces, a rare edible fungus with both nutritional and medicinal value, has garnered significant attention for its antioxidant properties. This study aims to elucidate the effects of various nutritional components on the antioxidant activity of Termitomyces. Through assays including FRAP, DPPH, ABTS, and •OH scavenging activity, strain XNQL025, which exhibits high antioxidant activity, was identified. Subsequent optimization of culture medium components using single-factor experiments and response surface methodology revealed that aspartic acid (Asp) significantly enhances the antioxidant capacity of this strain. Transcriptomic analysis showed that Asp activates key pathways, including glycolysis/gluconeogenesis, propanoate metabolism, amino sugar and nucleotide sugar metabolism, valine–leucine–isoleucine biosynthesis, and tryptophan metabolism, along with modulating the peroxisome and mitogen-activated protein kinase (MAPK) signaling pathways. These regulatory actions promote the synthesis of antioxidant compounds and establish a multi-layered antioxidant defense system comprising enzymatic (catalase) and non-enzymatic (leucine/chitooligosaccharides) components. The synergistic interaction between these systems significantly strengthens the antioxidant defense capacity of Termitomyces. This study is the first to elucidate the molecular network by which Asp enhances the antioxidant activity of Termitomyces, thereby providing a foundation for its development as a natural antioxidant.